Afghanistan Economic Update, April 2014 - Joya, Omar; Khan, Faruk (World Bank, Washington, DC, 2014)
Economic growth slowed considerably to 3.6 percent (estimated) in 2013 despite robust agricultural production, as heightened uncertainty surrounding the political and security transition led to a slump in investor and consumer confidence. Growth is projected to remain weak in 2014, while a smooth political and security transition would help restore confidence in the economy and enable a pickup in growth in 2015. Revenue collection continued to weaken in 2013, while Afghanistan's large security expenditure obligations and high aid dependence pose the risk of crowding out important civilian operating and development spending. Domestic revenues declined to 9.5 percent of GDP in 2013 from 10.3 percent in 2012 and the peak of 11.6 percent in 2011. The decline in revenue collections is a result of the economic slowdown as well as weaknesses in enforcement in both tax and customs administration. In light of tight resources, austerity measures in 2013 disproportionately affected civilian expenditures as security expenditures have continued to grow. A concerted effort will be required going forward to improve revenue mobilization, while at the same time safeguarding important civilian spending. In addition to managing the transition related uncertainty and underperformance, Afghanistan will need to stay focused on its medium term structural reform goals, which include: (i) ensuring fiscal sustainability by mobilizing revenue, securing grant assistance, and safeguarding non-security expenditures; (ii) supporting inclusive and job-creating private-sector led growth by unlocking the potential of the agriculture, services, and natural resource sectors and by tapping the potential of regional integration; (iii) continuing to improve upon the still low levels of human capital and skills; and (iv) continuing to strengthen institutions and governance.